A performance musical do zabumbeiro Quartinha - Dantas, Gledson Meira (2011)
The studies of musical practices developed in urban contexts have been gaining in recent decades, more and more space in ethnomusicological research and point to ample opportunities for research and important contributions, in relation to knowledge of the various directories and their producers in many aspects. This work proposes a study on the musical performance of Quartinha Zabumbeiro, based on the concept of performance as event and process, where they are considered not only the musicians performing, but the general context, involving the audience, the environment and the results of interaction among participants. Considering the general objective to examine and understand the features of the musical performance of Quartinha, the work is the cornerstone theoretical and methodological foundations of ethnomusicology and has significant contributions of musicology, organology, anthropology and ethnography. As data collecting instruments were used in literature, participant observation, the semi-structured interview, in addition to audio recordings, video and photography; these instruments were designed in order to tailor them to the needs of the survey, and were fundamental to the results obtained in the work. Even considering the general aspects of performance in the Quartinha various sets that have participated, with emphasis on groups of forró, the text highlights its performance in the work of the musician Santanna. From the analysis, we observed that the musical performance of Closet characterized by observation of other musicians, especially Zabumbeiros, the development of collective practice, inventiveness, and the construction of a personal style that has been socially recognized along its trajectory.